2005
DOI: 10.5897/ajb2005.000-3134
|View full text |Cite
|
Sign up to set email alerts
|

Shelf stability of agidi produced from maize (Zea mays) and the effects of sodium benzoate treatment in combination with low temperature storage

Abstract: The shelf stability of agidi produced from maize (Zea mays) during ambient temperature (30.0±1.5°C) storage and the effects of sodium benzoate treatment in combination with low temperature storage (12-14°C) was evaluated for eight weeks. Results indicates high total aerobic bacterial count (1.05x10 10 cfu/g) and fungi count (4.6x10 9 cfu/g) at the 12 th day of storage and thereafter, decrease gradually till the end of the storage period. Treatment with 0.15% sodium benzoate and refrigeration at 12-14°C drastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The moulds isolated from spoilt agidi samples were characterized as A. flavus, Penicillium spp, A. niger and Rhizopus spp. Morphological and physiological characteristics of the isolates agrees with the findings of Ogiehor et al (2005). Several authors have also detected and isolated most of theses spoilage organisms in fermented foods and beverages (Filtenborg et al, 1996;Corsetti et al, 1998;Pitt and Hocking, 1999).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The moulds isolated from spoilt agidi samples were characterized as A. flavus, Penicillium spp, A. niger and Rhizopus spp. Morphological and physiological characteristics of the isolates agrees with the findings of Ogiehor et al (2005). Several authors have also detected and isolated most of theses spoilage organisms in fermented foods and beverages (Filtenborg et al, 1996;Corsetti et al, 1998;Pitt and Hocking, 1999).…”
Section: Discussionsupporting
confidence: 84%
“…This was followed by wet sieving with the aid of a clean muslin cloth. The mixture was allowed to settle and the ogi slurry supernatant was decanted and packed in a jute bag (Ogiehor et al, 2005).…”
Section: Preparation Of Agidimentioning
confidence: 99%
“…Porridges general are produced primarily from cereals such as maize, sorghum, millet, acha [2] and are predominantly eaten in developing countries [2]. Madidi is basically consumed as breakfast meal with soup [3] or beans cake (akara/kose), weaning of infants and meal for patients [4]. Although, it is eaten by all population of both young and old [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used in the preservation of maize [12][13][14][15][16] some of which are drying and storage crib; mud or cement-plastered basket; brick bin; ferrocements bin (Ferrumba); postcosecha galvanized steel silos; in the modern-day technology, refrigeration system also can be used because it can be manipulated to give various conditions. Charles and Rogers [17] observed that overnight storage of fresh maize in wagon or truck can have a marked effect on their future storability.…”
Section: Introductionmentioning
confidence: 99%